A study of some variables biomechanics in clean and jerk for the world champions men and women - SALIH, MUSTAFA (Journal of Physical Education, 2023)
The researcher study variables biomechanics in clean jerk for both sexes men and women and differently ,but the weights light and heavy weight for men and women during the filming of world championship which held in Thailand 2007 where must that is the champion between these two groups to find out the facts of what is still not clear to promote the sport of weightlifting ,as feminist to find out the possibility of women in the sport of weightlifting Were selected random sample deliberate was chosen as the winner on the champions gold medal in clean and jerk Study were all variable speed time, divisions, highest Reached following There was clear difference in time towards M There was difference in the division towards F There was difference in speed towards M The researcher recommended the formation of teams with the economical in the effort weightlifting and taking into account the training age limit for women and the adoption of suspense in the training of women as recommended by researcher to continue such research and studies